FAKTOR -FAKTOR YANG MEMPENGARUHI PRAKTIK PERILAKU HIDUP BERSIH DAN SEHAT PADA MAHASISWA KOS DI PADUKUHAN KARANGMALANG YOGYAKARTA - LILI ARIANI (HB PRESS, 2018)
ABSTRACT The absence of awareness of Indonesian society on PHBS (clean and healthy behavior) on daily basis causes several diseases to emerge. This research was aimed to discover the factors affecting the practice of PHBS by the students in padukuhan Karangmalang. The research method employed in this research was survey using cross sectional framework. The subject were college students ranged form age 18 to 25 years old who live in Karangmalang district. The total sample of 130 respondents was obtained using simple random sampling. The data then underwent univariate,bivariate,and multivariate analysis. The result obtained showed that (53,1%)of the respondents were categorised as bad practitioner of PHBS and (46,9%) were categorised as good practitioner. The results also showed that there is a significant correlation between the knowledge of PHBS (p=0,002), attitude towards PHBS (p=0,000), the role of PHBS officer and PHBS (p=0,001), the availability of clean restrooms and PHBS (p=0,000), and the). The multivariate result showed that the role of the PHBS officer plays a significant factors in the practices of PHBS with the score of OR/Exp(B) 3,642 and CI 95%= 1,434-9,251. The conclusion of the research is that the knowledge of PHBS, attitude towards PHBS, the role of PHBS officer, the availability of clean restrooms, and can have significant correlation with PHBS and the most significant factor towards the practice of PHBS is the role of the PHBS officer. Keywords: Clean and healthy behavior, boarding students.